2014
DOI: 10.2306/scienceasia1513-1874.2014.40.268
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol production from cassava using a newly isolated thermotolerant yeast strain

Abstract: Efficient ethanol production using thermotolerant yeast strains was carried out with a newly isolated yeast strain called 267. Strains were isolated with an enriched technique consisting of a blackstrap molasses medium supplemented with 40 ml/l of ethanol at 25-28°C. The results revealed that 33 strains produced ethanol at 45°C in the cassava starch hydrolysate medium, pH 4.5, which was composed of 180 g/l reducing sugar and 0.5 g/l (NH 4 ) 2 SO 4 , with a shaking speed of 120 rpm. The highest ethanol concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
1
12
1
Order By: Relevance
“…The same trend was clearly observed when SSJ was used as a substrate for ethanol production. The promising strains, particularly S. cerevisiae KKU-VN8, produced much higher ethanol concentrations than that of the reference strain as well as those reported by Sree et al, 8 Tomás-Pejó et al, 64 and Kaewkrajay et al, 43 at 40 °C and 43 °C. These results may be attributable to the higher levels of stress tolerance exhibited by the potential strains during fermentation, leading to better ethanol production and the unique stress-tolerant mechanisms, allowing the yeasts cope with environmental stresses during ethanol fermentation, including the synthesis of Hsps and trehalose 50, 51, 52, 53.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The same trend was clearly observed when SSJ was used as a substrate for ethanol production. The promising strains, particularly S. cerevisiae KKU-VN8, produced much higher ethanol concentrations than that of the reference strain as well as those reported by Sree et al, 8 Tomás-Pejó et al, 64 and Kaewkrajay et al, 43 at 40 °C and 43 °C. These results may be attributable to the higher levels of stress tolerance exhibited by the potential strains during fermentation, leading to better ethanol production and the unique stress-tolerant mechanisms, allowing the yeasts cope with environmental stresses during ethanol fermentation, including the synthesis of Hsps and trehalose 50, 51, 52, 53.…”
Section: Discussionsupporting
confidence: 79%
“…Many studies have reported thermotolerant yeasts growing at temperature ranges similar to those described in this study; however, differential ethanol production was observed 8, 12, 15, 17, 42. The differences in ethanol production might be due to differences in natural sources for the isolation and strains of thermotolerant yeasts, in which this study differs from those reported by Limtong et al, 3 Yuangsaard et al, 15 Kwon et al, 17 Kaewkrajay et al, 43 and Charoensopharat et al 44 …”
Section: Discussioncontrasting
confidence: 69%
“…Edgardo et al [19] used glucose for the selection of thermotolerant yeast strains and obtained a good potential thermotolerant yeast S. cerevisiae that was able to produce approximately 75% of the theoretical ethanol yield at 40˝C. In addition to using glucose as a substrate, other carbon sources, such as sugarcane juice [13], xylose [41], sugarcane blackstrap molasses [42], and inulin [43] have also been used for screening and selecting thermotolerant yeasts.…”
Section: Isolation and Selection Of Thermotolerant Yeast Strainsmentioning
confidence: 99%
“…1.2-2.25% [16][17]35], but still lower than other reports i.e. 4.2-10.0% [12,15,20,[36][37][38][39][40], 28.18-29.33% [39,41].…”
Section: Fermentation Of Cassava Hydrolysate Filtratementioning
confidence: 91%
“…To improve the efficiency of sugar to ethanol conversion in a further experiment, some efforts in terms of starter will be considered to be applied, e.g. by feeding fresh starter (10% v/v) instead of dry yeast [17,36], applying immobilized yeast [40], or using superior yeast type [36][37]. Sugar concentration in fermentation media is also a factor to be considered, which sugar concentration of 10% showed the best effect on alcohol production [40].…”
Section: Fermentation Of Cassava Hydrolysate Filtratementioning
confidence: 99%